2018
DOI: 10.1007/s40093-018-0231-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing microbial population dynamics, enzyme activities and phosphorus availability indices during phospho-compost production

Abstract: Purpose This study assessed changes in bio-quality indices and plant available P released during aerobic-thermophilic cocomposting of different mix ratios of non-reactive ground phosphate rock (GPR) with poultry and cattle manures. Methods Aerobic-thermophilic co-composting of different mix ratios (5:5, 8:2, 7:3 and 9:1) of non-reactive GPR with poultry and cattle manures was carried out. Compost piles without GPR addition were included as control. Compost samples were taken at mesophilic, thermophilic, coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
3
0
3
Order By: Relevance
“…Chicken farming can cause problems for the environment, especially when there is a buildup of ammonia from chicken manure that contains nitrogen. The amount of ammonia will increase if it is decomposed by microbes [27]. Conditions of high humidity, warm temperatures and above-normal pH can exacerbate the situation [28].…”
Section: Kub Chicken Business Sustainabilitymentioning
confidence: 99%
“…Chicken farming can cause problems for the environment, especially when there is a buildup of ammonia from chicken manure that contains nitrogen. The amount of ammonia will increase if it is decomposed by microbes [27]. Conditions of high humidity, warm temperatures and above-normal pH can exacerbate the situation [28].…”
Section: Kub Chicken Business Sustainabilitymentioning
confidence: 99%
“…Populasi cendawan terendah pada minggu terakhir pengukuran terdapat pada bahan kompos campuran kotoran ayam (Gambar 1). Hasil penelitian ini sejalan dengan penelitian Kutu et al (2019) yang menyatakan bahwa kelimpahan mikroba (bakteri, aktinomiset dan fungi) pada kompos kotoran ternak sapi dan sejenisnya lebih tinggi dan berbeda nyata dengan kelimpahan mikroba pada kompos kotoran ternak unggas. Populasi cendawan pada bahan kompos campuran kotoran kambing dan kotoran ayam cenderung naik pada minggu ke-2 (Gambar 1).…”
Section: Hasil Dan Pembahasanunclassified
“…Kelimpahan CPF pada kompos campuran kotoran sapi terjadi pada minggu ke-3 sedangkan kompos campuran kotoran ayam terjadi pada minggu ke-5. Jenis material kompos yang berbeda juga menyebabkan jenis, populasi dan aktivitas mikroba yang berbeda pula (Kutu et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Since, the primers of phoD used to encode the alkaline phosphatase covers a high diversity of bacteria and fungi, with a stronger incidence on bacteria (Bergkemper et al, 2016), our results on phoD abundance and its relationships with the compost's physicochemical properties ( Supplementary Table S3 and Table 5), indicate that not only the PSF but also phosphate-solubilizing bacteria may take parts in the mineralization of P, as we already stated above. However, Kutu et al (2018) also reported that the release of alkaline phosphatase was tightly linked to the activity of fungi.…”
Section: Relationships Between Compost's P Fractions and Microbiologimentioning
confidence: 99%